2022
DOI: 10.1029/2021ja029934
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Plasma Bubbles Observed at Dawn and After Sunrise Over South America During the 2015 St. Patrick's Day Storm

Abstract: Equatorial Plasma Bubbles (EPBs) over South America have been studied extensively over the years. The EPBs are defined as plasma depletion formed by Rayleigh-Taylor Instability (RTI) processes (Kelley, 2009). Different instruments and methodologies can be used to detect these EPBs, such as Ionosondes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Regarding the generation of near‐sunrise EPB during geomagnetic storms, previous studies suggested that the disturbance dynamo electric field or the prompt penetration of overshielding electric field associated with sudden northward turning of IMF B z could be the potential driving force (e.g., Carmo et al., 2022; Tulasi Ram et al., 2015). In the present study, whereas the solar wind speed still remained high toward the dawn sector, the variation of IMF B z was no longer as significant as that around sunset (Figures 8a and 8b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the generation of near‐sunrise EPB during geomagnetic storms, previous studies suggested that the disturbance dynamo electric field or the prompt penetration of overshielding electric field associated with sudden northward turning of IMF B z could be the potential driving force (e.g., Carmo et al., 2022; Tulasi Ram et al., 2015). In the present study, whereas the solar wind speed still remained high toward the dawn sector, the variation of IMF B z was no longer as significant as that around sunset (Figures 8a and 8b).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the generation of near-sunrise EPB during geomagnetic storms, previous studies suggested that the disturbance dynamo electric field or the prompt penetration of overshielding electric field associated with sudden northward turning of IMF B z could be the potential driving force (e.g., Carmo et al, 2022;Tulasi Ram et al, 2015).…”
Section: On the Possible Generation Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested that the EPBs observed at dawn or post-sunrise periods are the remnant of post-sunset EPBs [18][19][20]. Contrary to this, it is also reported that the pre-reversal enhancement (PRE) of the ionospheric F layer peak under the influence of nighttime eastward DDEF triggered the generation/enhancement of irregularities [12,[21][22][23]. The ionospheric irregularities (or EPBs/ESF) during geomagnetic storms cause massive phase fluctuations and amplitude scintillations impacting satellite signals [24,25].…”
Section: Introductionmentioning
confidence: 99%